2011
DOI: 10.1113/jphysiol.2010.200915
|View full text |Cite
|
Sign up to set email alerts
|

Nav1.7 mutations associated with paroxysmal extreme pain disorder, but not erythromelalgia, enhance Navβ4 peptide‐mediated resurgent sodium currents

Abstract: Non-technical summary Abnormal pain sensitivity associated with inherited and acquired pain disorders occurs through increased excitability of peripheral sensory neurons in part due to changes in the properties of voltage-gated sodium channels (Navs). Resurgent sodium currents (I NaR ) are atypical currents believed to be associated with increased excitability of neurons and may have implications in pain. Mutations in Nav1.7 (peripheral Nav isoform) associated with two genetic pain disorders, inherited erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 38 publications
10
103
1
Order By: Relevance
“…To measure this current in a heterologous expression system, a peptide with the sequence of the ␤4 C-terminal section was added to the pipette solution (13). In contrast to A1632T (Fig.…”
Section: A1632e (Linked To Iem and Pepd) But Not A1632t (Linked To Imentioning
confidence: 99%
See 2 more Smart Citations
“…To measure this current in a heterologous expression system, a peptide with the sequence of the ␤4 C-terminal section was added to the pipette solution (13). In contrast to A1632T (Fig.…”
Section: A1632e (Linked To Iem and Pepd) But Not A1632t (Linked To Imentioning
confidence: 99%
“…Slowed transition from the open to the inactivated state, as observed for A1632E, promotes the occurrence of resurgent currents (13). To measure this current in a heterologous expression system, a peptide with the sequence of the ␤4 C-terminal section was added to the pipette solution (13).…”
Section: A1632e (Linked To Iem and Pepd) But Not A1632t (Linked To Imentioning
confidence: 99%
See 1 more Smart Citation
“…The (adult) patients with the M1627K mutation were carbamazepine-responsive with 600 mg/d, whereas a dose of 400 mg/d in a two-year-old boy weighing 8 kg merely halved the frequency of the pain attacks to one every two days. A number of voltage-clamp studies have shown that the M1627K mutation has a marked effect on fast inactivation of NaV1.7 [1][2][3] and resurgent sodium currents [3]. However none of these electrophysiological studies assessed the effect of carbamazepine in the M1627K mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The SIFT, PolyPhen-2, MutationTaster and Align GVGD prediction tools all suggested that Met1627Arg was likely to affect protein function. Lastly, another mutation of the same amino acid (Met1627Lys) has been reported in carbamazepine-responsive paroxysmal extreme pain disorder [2,3].…”
Section: Case Studymentioning
confidence: 99%